Analisis Keterampilan Argumentasi Ilmiah Siswa MTs pada Materi Bumi dan Tata Surya - Eka Ananda Diah Permatasari; Wahyuni Fajar Arum; Jariyah, Ita Ainun (Wacana Akademika: Majalah Ilmiah Kependidikan, 2025)
This study aims to determine the level of argumentation skills among students at MTsN 1 Surabaya on the subject of Earth and the Solar System. This study is quantitative descriptive in nature. The respondents in this study were 31 students in class VII-D. Data were collected through a 10-question scientific argumentatiom skills test validated by science teachers. The results of the argumentation skills research at MTsN 1 Surabaya showed that the percentage of the claim indicator was 80.64%, indicating that students were good at making claims. The evidence indicator, with a percentage of 58.17%, was classified as adequate, while the warrant indicator, with a percentage of 48.17%, was classified as inadequate. Differences in the quality of arguments may occur due to differences in the ability to construct structured arguments based on scientific concepts and limited understanding, which makes it difficult for students to connect claims with evidence and warrants.